Quality of life assessment of breast cancer patients in Saudi Arabia - Tahani H Nageeti; Huda R Elzahrany; Aisha O Gabra; Arwa A Obaid; Raid A Jastania (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: To assess the quality of life (QOL) of females with breast cancer in Saudi Arabia and its association with patients' demographic, social, and clinical data. MATERIALS AND METHODS: This analytical cross-sectional study was conducted among breast cancer patients attending King Abdullah Medical City, Makkah. Participants were asked to complete a self-administered structured questionnaire. We utilized the validated Arabic version of the European Organization for Research and Treatment of Cancer QOL-C30 (EORTC-QOL-C30) and breast cancer module QLQ-BR23 (EORTC-QOL-BR-23). Data were analysed using SPSS; mean and standard deviation computed for continuous variables, and percentages for categorical variables. Student's t-test performed to compare mean scores for various groups. RESULTS: Eighty-eight women participated in the study. The participants had a mean global health score of 64.0, standard deviation (SD) = 27.7. Of the functional scales, role functioning scored the highest (mean 71.2, SD = 31), while social and emotional functioning scored the lowest, (mean 57 SD = 35.8) and (mean 59.5 SD = 32), respectively. On the symptom scales, the most troubling symptoms were fatigue and insomnia, (mean 48.86 SD = 29.4) and (mean = 48, SD = 35), respectively. On the disease-specific tool (QLQ-BR23), body image and future perspective scored the lowest with a mean of 60.2 SD = 35 and 42.0 SD = 39.6, respectively. The most distressing symptom was hair loss (mean 61.56 SD = 41). CONCLUSIONS: Our population showed an acceptable overall global health score. However, they scored low on the important functional and symptoms domains. This study implies that patient age, social, and physical factors were possible determinants of global health and QOL scores. The healthcare system of Saudi Arabia should, therefore, address all these different aspects of QOL of breast cancer survivors.